Peran LBH Dan Tantangan Penyelesaian Kriminalisasi Anak Dibawah Umur - Naufal Rafi Sadad Putra Ramadhan; Mega Dewi Ambarwati (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Many minors or minors are dealing with the law, whether it is a perpetrator or a victim. The rules and guidelines for the settlement of legal cases involving the subject or object of the minor in the event or legal event have certainly been stipulated through the SPPA Law No. 11 of 2012. However, we need to ensure whether the rules and regulations regarding the guidelines for handling minor cases can be realized correctly. Because there are still many who are accidentally or even deliberately by law enforcement in Indonesia, violating the standardization of handling minors which makes their rights not fulfilled properly. With the existence of lbh (legal aid institution), it is possible to ensure that the community can be guaranteed every right in dealing with the law. In this journal I try to describe it based on the research method I use, namely normative-empirical. So it is hoped that through this journal that I write can be useful in evaluating the application of law in society because I am writing this not only based on research from laws and regulations and also existing journals, but also the experience of practice that I did through an internship at the SCCC (Surabaya Children Crisis Center).